Emergency surgical decompression and long-term survival of glioblastoma presenting in coma in old age: case report and review of prognostic factors. Issue 7 (26th July 2022) - McKinley, Aidan; Lammy, Simon; James, Allan; Stan, Alexandru; Barrett, Chris
ABSTRACT: We present a case demonstrating that older age does not exclude long-term survival with glioblastoma. This is a malignant neoplasm with a median life expectancy of 14 months in patients treated with radical intent. Survival is dependent on several independent and interacting prognostic factors of which advancing age is a negative factor. We present a septuagenarian with a 3.5-year survival following aggressive management. The potential to improve glioblastoma survival in an elderly population by examination of additional prognostic factors and identifying biomarkers warrants further research.